Characterizing conjugative plasmids from an antibiotic-resistant dataset for use as broad-host delivery vectors - Loyola Irizarry, Héctor G.; Brito, Ilana L. (Frontiers in Microbiology, 2023)
Human microbiome engineering is increasingly proposed as a way to modulate health outcomes. However, one of the current limitations to engineering microbial communities in situ is delivery of a genetic payload for introducing or modifying genes. Indeed, there is a need to identify novel broad-host delivery vectors for microbiome engineering. Therefore, in this study, we characterized conjugative plasmids from a publicly available dataset of antibiotic-resistant isolate genomes in order to identify potential broad-host vectors for further applications. From the 199 closed genomes available in the CDC & FDA AR Isolate Bank, we identified 439 plasmids, of which 126 were predicted to be mobilizable and 206 conjugative. Various characteristics of the conjugative plasmids, such as size, replication origin, conjugation machinery, host defense mechanisms, and plasmid stability proteins, were analyzed to determine these plasmids’ potential host-range. Following this analysis, we clustered plasmid sequences and chose 22 unique, broad-host range plasmids that would be suitable for use as delivery vectors. This novel set of plasmids will provide a valuable resource for engineering microbial communities.